microRNA-203 Targets Insulin-Like Growth Factor Receptor 1 to Inhibit Trophoblast Vascular Remodeling to Augment Preeclampsia - Zhang, Li; Lv, Yuxia (American Journal of Perinatology, 2021)
Objective Preeclampsia (PE) is a pregnancy-specific condition featured by high blood pressure, edema, and proteinuria. Research about the role of microRNA (miR)-203 in PE remains insufficient. This experiment is designed to investigate the specific role of miR-203 in trophoblasts in PE.Study Design miR-203 expression in placenta tissues of normal pregnant women and PE patients was examined to analyze the relevance between miR-203 and PE diagnostic efficiency and between miR-203 and blood pressure (systolic pressure and diastolic pressure) and proteinuria of PE patients. miR-203 expression was downregulated in hypoxia-cultured trophoblasts using miR-203 inhibitor to assess matrix metalloproteinase-9 (MMP-9) level. Then, the angiogenesis of trophoblasts with different treatments was determined. Subsequently, the target relation between miR-203 and insulin-like growth factor receptor 1 (IGF-1R) was predicted and verified. Additionally, the effect of IGF-1R in the mechanism of miR-203 modulating trophoblast vascular remodeling was detected.Results miR-203 was overexpressed in the placenta of PE patients and it acted as a promising diagnostic indicator for PE. Moreover, miR-203 was positively associated with blood pressure (systolic pressure and diastolic pressure) and proteinuria of PE patients. miR-203 silencing in hypoxia-cultured trophoblasts enhanced trophoblast vascular remodeling. Mechanically, miR-203 bound to IGF-1R to suppress its transcription. IGF-1R downregulation counteracted the promotive effect of miR-203 silencing on trophoblast vascular remodeling.Conclusion miR-203 was overexpressed in PE, and it targeted IGF-1R to limit trophoblast vascular remodeling.Key Points
Keywords: microRNA-203; IGF-1R; preeclampsia; trophoblast; vascular remodeling; posttranscriptional regulation